Comparison Curriculum Analysis between Indonesian KTSP 2006 and 2013 Curriculums - Barata, Alvin; Patria, Lilis; Shilvani, Shilvani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2024)
Education has become a part of human life. It is given to individuals differently depending on where the educational activities take place. In order to maintain the consistency of education in certain areas, there is a need for a curriculum that defines the materials and learning standards that must be taught and achieved in educational institutions based on the customs of each area around the world. One method of curriculum implementation is through textbooks. They are tools in which curriculum materials and standards are implemented to support teaching and learning activities. Textbooks always have problems with the content related to the implemented curriculum. There is a need for evaluation to assess the effectiveness and efficiency of textbooks. This study examines the existing implemented curriculum with the textbook contents. Two textbooks,